Family function and adolescent altruistic behavior: the chain mediating role of extraversion personality and perceived social support - Gao, Tao; Cui, Hongbo; Bi, Xiaoyan; Qing, Zaihua; Chen, Weiyu; Shi, Keke; Song, Meidan; Ma, Yankun (Frontiers in Psychology, 2024)
This study examines the relationship between family function and altruistic behavior in adolescents, with a focus on the mediating roles of extraverted personality and perceived social support. High school students from Guangdong Province in the survey, which utilized the Family APGAR Questionnaire, extraversion personality Scale, Perceived Social Support Scale, and Altruistic Behavior Scale. resulting in 972 valid responses.. The findings revealed that family function directly predicted altruistic behavior, with extraversion and perceived social support serving as significant mediators. Furthermore, a chain mediation effect was identified, where both extraversion and perceived social support sequentially mediated the relationship between family function and altruistic behavior. These results underscore the importance of family dynamics in shaping prosocial behavior and suggest that interventions aimed at fostering positive family environments,promoting extraversion, and strengthening social support networks may enhance altruistic tendencies in adolescents.in adolescents.